PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, REWARD & PUNISHMENT TERHADAP DISIPLIN KERJA GURU SEKOLAH DASAR ISLAM DI WILAYAH LAMPUNG - Elistatia, Usi; Anggoro, Bambang Sri; Hadiati, Eti (Jurnal Manajemen Pendidikan, 2026)
This This research aims to analyze the influence of principal leadership, reward, and punishment on teacher work discipline at SD Islam Assalam Bandar Lampung and SDIT Baitul Insan Pesawaran. A quantitative approach with an explanatory survey method was employed. The population consisted of 73 teachers from both schools, with the total population being used as the sample (saturated sampling). Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 27. The results indicated that simultaneously, principal leadership, reward, and punishment had a significant effect on teacher work discipline with an F-value of 49.750 and a determination contribution (R2) of 68.4%. Partially, all three variables also had a positive and significant influence on teacher work discipline. Principal leadership provided an effective contribution of 34.45%, reward contributed 26.66%, and punishment contributed 7.24%. These findings imply that strengthening leadership and an equitable reward system are key factors in enhancing teacher professionalism and discipline within Islamic educational institutions.